Paralympic legacy: Exploring the impact of the games on the perceptions of young people with disabilities - Coates, J.; Vickerman, P. B. (Adapted Physical Activity Quarterly, 2016)
The London 2012 Olympic and Paralympic Games aimed to deliver a legacy to citizens of the United Kingdom, which included inspiring a generation of young people to participate in sport. This study aimed to understand the legacy of the Paralympic Games for children with disabilities. Eight adolescents (11-16 yr) with physical disabilities were interviewed about their perceptions of the Paralympic Games. Thematic analysis found 3 key themes that further our understanding of the Paralympic legacy. These were Paralympians as role models, changing perceptions of disability, and the motivating nature of the Paralympics. Findings demonstrate that the Games were inspirational for children with disabilities, improving their self-perceptions. This is discussed in relation to previous literature, and core recommendations are made.